Excess noise reduction with ear protector applying mathematical algorithm: A case of medium density fiber industry. (July 2020) - Khan, Sohail; Noor, Ishrat; Habib, Tufail; Waseem, Muhammad
Consistent exposure to elevated sound levels results in noise health effects. The industrial environment represents a major source of such effects. There is significant variation in noise at different sections of such industries due to which most of the workers are exposed to these sounds at one or another level. In this study, a noise level measuring methodology is used for fixed and moving workers. This article introduces an algorithm for optimum selection of earmuff and earplug for different working places depending upon the exposure to noise. Medium density fiber industry is considered as a case for this study. It considers workers who are busy at a single point and face a consistent amount of noise as well as the workers who move and are exposed to a varying level of the noise. Noise level meters are used to measure the noise level at different points. At each point, the average value of the samples is taken. Based on the data collected, earmuff with high noise reduction rate is assigned to the workers closed to the machines. Implementation of the developed algorithm reduced the effect of noise on workers by 6.9%, 5%, and 16.3% for the chipper machine, pneumatic fan, and sanding machine, respectively, that were identified as the major source of noise at medium density fiber industry. This percentage reduction helped the workers to bring them to the optimum safe level of noise that is 85 dB and protect them from hearing loss severity due to frequency variations.